Intellectual property rights, imitation, and development. The effect on cross-border mergers and acquisitions. Issue 2 (17th February 2019) - Campi, Mercedes; Dueñas, Marco; Barigozzi, Matteo; Fagiolo, Giorgio
ABSTRACT: In this paper, we analyze whether the recent global process of strengthening and harmonization of intellectual property rights (IPRs) affects decisions of cross-border mergers and acquisitions (M&As). We investigate if IPRs have a differential effect across sectors of different technology content and for countries of different development level. Also, we study how imitation abilities of target countries interact with the tightening of IPRs. Using data for the post-TRIPS period (1995–2010), we estimate an extended gravity model to study the bilateral number of M&As, including a measure of the strength of IPRs systems on target countries and a set of control variables usually considered as determinants of M&As. The estimation results verify the gravity structure for M&As and show that IPRs –and enforcement– influence decisions of cross-border M&As in all sectors regardless of their technological content. However, IPRs are more important in countries with high imitation abilities and in sectors of high-technology content. Furthermore, a strengthening of IPRs leads to a larger increase of M&As in developing countries than in developed countries. These results call the attention on the possible implications for least developed economies and challenge the adequacy of a globally harmonized IPRs systems.